CFD Prediction of Heterogeneities in the Scale up of Liquid-Liquid Dispersions (2014)
In this work simulations were developed in order to allow the examinations of heterogeneities in the scale up of liquid-liquid dispersions (oil-water) in 3 and 300 L stirred tank bioreactors using CFD simulations (Computational Fluid Dynamics). The effects of turbulence, rotating flow, drop breakage were simulated by using the k-e, MRF (Multiple Reference Frame) and PBM (Population Balance Model), respectively, providing detailed information of important bioreactor conditions. CFD modeling predicts with good approach hydrodynamic trends which can affect the liquid-liquid dispersion process of large scale bioreactors. Motivated by these results, CFD simulations are qualified as a very promising tool for predicting hydrodynamics and drop sizes especially useful for liquid-liquid applications which are characterized by the challenging problem of emulsion stability due to undesired drop and heterogeneities in the scale up process.